The Economic Analysis of Law in Pakistan (The Pakistan Development Review, 2020)
One of the most important functions of law is to assign rights and liabilities in such a way that disputes do not arise. The failure to prevent disputes in a society indicates that the structure of the law is inefficient. Since the focus of law and economics is on efficiency (see Box 1) and how people respond to incentives, one way to carry out the economic analysis of the law is to use the framework of market capitalism. Driven by the idea of the invisible hand, the fundamental point of capitalism is that individuals should be able to use their capital freely, without the state’s interference. It implies that individuals’ legal ability to move capital should be frictionless.